FOOD LABEL EVALUATION IN ADOPTION PROCESS OF FUNCTIONAL FOOD - Suci Paramitasari Syahlani (Journal of Management and Business, 2008)
The objective of this research is to identify the effect of food label information on the adoption process of functional food. The laboratory experiments were conducted with specific and general food label as the experiment treatment. One hundred and ninety-nine subjects were selected; those were the ones who served as decision makers in buying food for themselves or their families. The data was analyzed with the compare means analysis which are paired samples test and independent samples test. The result shows that food label evidently increases subjective and objective knowledge. However, this study does not prove that specific food label with institution certification increases knowledge better than general food label. Consistently, perceive persuasion can not be strengthen by the institution certification in specific food label.